In the Beginning … Creation - Varah, Mahaingam; Shipton, Warren A.; Vidacak, Zeny (11th International Scholars Conference, 2019)
The creative activities involved all members of the Godhead. A possible delineation of their roles was investigated. Further, a rationale for creation was sought given knowledge that the progenitors of the race would betray their trust. The historical-grammatical approach was used in textual understanding. The Genesis account was compared with parallel passages and this was combined with variants in word meanings and was contrasted with the message conveyed by other passages. An understanding of God’s character and the defining features of His government were used to answer the second research question. Accounts given by the apostle John and those recorded at Jesus’ baptism and at the preadvent judgment described by Daniel suggests that at creation the Father spoke, the Son initiated the creative acts, and the Spirit performed an organizational and activating role. The cooperative activities of the members of the Godhead illustrate the reality of the operation of love (agape type) from the beginning. Further analysis showed that the creation of this world represented an expression and the triumph of love in the face of knowledge that humans would fail in the trust given them. Love also explains how the foundational elements of God’s character and government fit together—concepts of righteousness, justice, truth, mercy and faithfulness— and hence illustrates how human salvation (recreation) is possible. Creation is seen as a planned event dashing the claims of evolution that existence preceded essence. The existence of a widespread sense of right and wrong, of human sexuality, of the amazing analytical and creative capacity of the human mind speaks that essence preceded existence. This is confirmed by the day to day experiences of those who permit God to undertake the recreation of His character image in them. Further research on the questions raised is merited.